(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2007)
We present a study of Late Pleistocene fossil bird remains from Ingarano (Apulia, SE Italy), based on the revision of previously published material and the study of unpublished fossils bones. New field observations make it possible to simplify the stratigraphy of the deposit compared to previous work. The systematic study of the fossil bird bones revealed the presence of 15 taxa, including two hypothetical ones: Circus aeruginosus, Buteo rufinus, Aquila chrysaëtos, Falco columbarius, Falco cherrug, Alectoris graeca, Perdix perdix, Columba livia, Otus scops, Nyctea scandiaca, Nyctea scandiaca vel Bubo bubo, Athene noctua, Pyrrhocorax graculus, Pyrrhocorax pyrrhocorax, Corvus corone, Corvus corone vel Corvus frugilegus, Corvus corax. Our detailed study also helps improve the taphonomical interpretation of the deposit: the remains from the lower layers were accumulated after mammalian predator activity and were transported over short distances, while the ones from the upper layers show sings of intense transport, such as fractures and surface abrasion. Two different bird assemblages were recognized, respectively from the lowermost and the upper layers of the clastic succession exposed in the Ingarano deposit; this difference is also confirmed by the fossil mammal remains. The systematic study makes it possible to make palaeoenvironmental and palaeoclimatic reconstructions: both assemblages indicate open environments, and the taxa of the lower layers indicate the presence of woods and wetlands with colder characteristics, while birds of the upper layers indicate drier and warmer conditions. This analysis, and the dating established through geochemical analyses and study of lithic artefacts, lead us to date the formation of the Ingarano deposit to the Late Pleistocene, in particular to the MIS 3. The presence of a layer dated to the MIS 2 at the base of the succession indicated in previous works cannot be confirmed.